Structural Studies on Staphylococcus aureus Quorum Sensing Proteins AgrA and AgrB - Warwick, Thomas (2021)
Staphylococcus aureus is a human commensal pathogen notorious for the number and severity of infections it may cause and is endemic in hospitals worldwide. Virulence in S. aureus is partially controlled by a Quorum Sensing (QS) feedback circuit called agr (accessory gene regulator) which comprises four genes agrB, agrD, agrC, and AgrA that together regulate expression of major virulence factors. The activating switch of the QS loop requires the LytTR-type response regulator protein AgrA to bind to its cognate promoters to trigger gene expression. At present comprehension of the mode of AgrA dimerisation resulting from interaction with promoter DNA, and the asymmetry existing in the AgrA dimer, as a result of binding the two linear repeat sequences which comprise each promoter DNA, is absent. The crystal structure of AgrA bound to the upstream linear repeat binding site of the P2 promoter has been solved at 4.8 Å from crystals containing 67 % solvent. The crystal structure exhibits an extremely hydrophobic patch that mediates a dimer that closely resembles physiological dimers of other response regulators such a ComE, FixJ, and LytR. Mutation of either of two proximal cysteine residue pairs that are conserved amongst all staphylococcal AgrA phosphate-receiving domains was shown to retard cell growth during agr dormancy. The molecular envelope of a beryllium trifluoride-activated AgrA dimer bound to the P3 promoter was constructed from small-angle X-ray scattering measurements and shows a bend of ~ 55 ° imposed on the DNA by AgrA. AgrB is responsible for processing the linear precursor protein AgrD into the mature QS signal molecule, and is the archetypical member of the AgrB family of proteases for which there is no experimental structural data. Consequently, little is understood about the mechanism of AgrD processing and transport out of the cell. A robust purification of AgrB solubilized into a number of detergents is presented. T7 western blotting failed to show any sample activity in vitro, however, circular dichroism measurements indicate that the sample is folded, primarily α-helical and exhibits a melting temperature of 63 °C. Crystallisation experiments were performed in surfo and attempted in meso, however, no crystals were obtained. Preliminary negative staining electron micrographs and an atomic AgrB model are presented and discussed with respect to improving sample suitability for structural studies. The purification protocol developed was used to prepare AgrB for nanobody crystallisation chaperone generation at VIB nanobody core. The results of this work provide structural evidence that agr-dependant virulence factor upregulation in S. aureus occurs through bending of promotor DNA by AgrA. A hitherto undiscovered cysteine pair in the crystal structure of full-length AgrA suggests that AgrA may encode an additional oxidative checkpoint to QS in S. aureus. Whether this cysteine pair constitutes a genuine oxidative checkpoint or is simply required for protein stability in vitro requires further investigation, however.